19. OUTCOMES OF HAND FRACTURE TREATMENTS BY TRANSVERSE PERCUTANEOUS K-WIRE FIXATION (Vietnam Journal of Community Medicine, 2024)
Background: Hand fractures are relatively common, accounting for about 10% of all fractures, of which more than 70% are in working-age patients. Hand fractures can be treated conservatively or surgically, with a variety of fixation from closed surgery with K-wire or external fixation or open surgery with plate fixation. Minimally invasive surgery by transverse percutaneous k-wire fixation brings many benefits, however currently in Vietnam there are no reports on the results of treatment with this method..Objective: We aim to research clinical features and radiographic characteristics as well as evaluate the outcomes of metacarpal fractures treatment by transverse percutaneous K-wire fixation at Pleiku City General Hospital.Methods: A cross-sectional study was conducted on 11 patients who had metacarpal fractures treatment by transverse percutaneous K-wire from January 2021 to September 2022 at Pleiku City General Hospital.Results: 11 patients with 14 metacarpal fractures were treated with K-wire. The majority of patients had 1 bone fracture (72.7%), right arm fracture (81.8%), and closed fracture (81.8%), metatarsal shaft fractures (57.1%). Surgery time is quite fast (average 30 minutes). Most metacarpals heal after 2 months. Delayed healing occurred in 1 patient at a rate of 3.23%. 1 case with infected pin site among the total number of people surveyed.Conclusions: Through the research, we realized transverse percutaneous K-wire fixation in treating metacarpal fractures helps immobilize the fracture well, minimally invasive surgery, thus limiting pain and blood loss, allowing early mobilization, which is the key to achieving results, good function, avoiding joint stiffness as well as reduced or loss of hand function.
Keywords: Metacarpal fractures, Kirschner wire, minimally invasive surgery.